Pemanfaatan Lampu Pijar untuk Pencahayaan Buatan pada Photovoltaics sebagai Alternatif PLTS di Laboratorium Energi Terbarukan - Warsono, Warsono; Sunardi, Sunardi (JURNAL SIMETRIK, 2025)
This research was conducted to address the challenges of conducting solar panel practicum in the Energy Engineering laboratory during cloudy or rainy weather by developing a simulation module for solar panel experiments using incandescent lamps as the light source. The testing and analysis revealed that solar panel efficiency is higher under sunlight (5.64% at 504 W/m²) compared to incandescent lamps (5.04% at 500 W/m²), with a more pronounced efficiency drop under lamp lighting due to rising temperatures. When temperatures exceed 40°C, a significant decline in efficiency occurs, with rates of 0.106/°C for the lamp and 0.093/°C for sunlight. The solar panel simulation module using incandescent lamps can serve as a practical solution for conducting experiments during overcast or rainy conditions. Keywords: Solar panels, Incandescent lamps, PLTS practicals